2009
DOI: 10.1007/s11104-009-9889-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cadmium and copper effect on phenolic metabolism, mineral nutrients and stress-related parameters in Matricaria chamomilla plants

Abstract: Cadmium and copper uptake and its consequence for activity of selected enzymes of phenolic metabolism, phenolic acids accumulation, quantity of mineral nutrients and stress-related parameters in Matricaria chamomilla plants exposed to 60 μM and 120 μM for 7 days has been studied. Cu content in the above-ground biomass was ca. 10-fold lower compared to Cd and amount of Cd in the methanol-soluble fraction was lower than in the water-soluble fraction. "Intra-root" Cd represented 68% and 63% of total Cd content at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
91
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(102 citation statements)
references
References 38 publications
10
91
1
Order By: Relevance
“…Higher correlation coefficients for FRAP were obtained in comparison with the DPPH test system. Oxidative stress due to heavy metal toxicity resulted in an increase in the activities of antioxidant metabolites such as phenolic compounds that participate in quenching reactive oxygen species (Kovačik et al, 2009). Our results indicate that the O. majorana antioxidant potential, defined by the concentration of phenolic compounds and flavonoids, considerably increases as a result of EEZ 35 and EEZ 54 application.…”
Section: Discussionmentioning
confidence: 99%
“…Higher correlation coefficients for FRAP were obtained in comparison with the DPPH test system. Oxidative stress due to heavy metal toxicity resulted in an increase in the activities of antioxidant metabolites such as phenolic compounds that participate in quenching reactive oxygen species (Kovačik et al, 2009). Our results indicate that the O. majorana antioxidant potential, defined by the concentration of phenolic compounds and flavonoids, considerably increases as a result of EEZ 35 and EEZ 54 application.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Kováčik & Klejdus (2008) and Kováčik et al (2009) demonstrated high levels of phenolic acids in tissues rich in copper, suggesting that this mineral is an important enzyme activator for the synthesis of these compounds (by PAL). Another interpretation of the increased levels of phenolic compounds in these tissues, suggested by the same authors, is that this is associated with a mechanism of tolerance to Cu, since Cu is a catalyst for redox reactions that can produce free radicals harmful to the plant; consequently, increased levels of phenolic compounds have two goals: to decrease the concentration of free Cu in plant tissue by the reaction of this with phenols, and to minimize the deleterious effects of free radicals formed, through the antioxidant action of the phenolic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolism of several phenols has been reported to change under Cu and Cd stress indicating a putative role of these compounds in heavy metal detoxification by decreasing the presence of the free metal ions (Kováčik et al, 2009). Lignin accumulation has also been described as a consequence of Cu toxicity (Lequeux et al, 2010) but whether this is related to a heavy metal defence mechanism is still not clear.…”
Section: Other Non Enzymatic Substances Involved In Heavy Metal Tolermentioning
confidence: 99%